The Genesis record a scientific and devotional commentary on the book of beginnings - Morris, Henry Madison, 1918- (Grand Rapids, MI Baker, 1976)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Genesis -- commentaries